Menakar Peluang Bonus Demografi Kedua Indonesia: Pendekatan Daya Dukung Ekonomi dan Kekayaan Pensiun - Yusa, I Gede Putu Dharma (Seminar Nasional Official Statistics, 2024)
After the first demographic dividend, Indonesia hopes to achieve a second demographic dividend through by enhancing productivity. A key strategy involves transforming economic ratio into accumulated pension wealth. Therefore, this study aims to investigate the potential and pathways for Indonesia's second demographic dividend from pension wealth perpective in the form of savings, physical investments, and pension funds. This research uses panel data from 34 provinces over the period 2001-2023, obtained from BPS-Statistics Indonesia, Bank Indonesia, and the Indonesia Financial Services Authority (OJK). The results show that Indonesia has the opportunity to achieve a second demographic dividend through the pension wealth pathway. In the first phase, economic support ratio successfully increased per capita income by around 2 percent per year. This dividend then boosted pension wealth through savings, physical investment, and pension funds per capita by 2,160 percent; 1,036 percent; and 1,330 percent, respectively. The decomposition by age shows that the growth of the working-age population also successfully increased per capita savings and physical investment.